Parasitism by Sphincterodiplostomum musculosum (Digenea, Diplostomidae) metacercariae in the eyes of Steindachnerina insculpta (Characiformes, Curimatidae) - Brandão, Heleno [UNESP]; Yamada, Fabio Hideki [UNESP]; Toledo, Gislayne de Melo [UNESP]; Acosta, Aline Angelina [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo Jose da [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
New occurrences and effects of parasitism by metacercariae in fish eyes have recently been discussed in many studies. The aim of the present study was to evaluate the infection levels of the eye flukes Sphincterodiplostomum musculosum Dubois, 1936 (metacercariae) in Steindachnerina insculpta (Fernadez-Yepez, 1948) from three ecosystems under the influence of the Jurumirim reservoir (Paranapanema, Taquari and Veados Rivers). A total of 174 fish specimens were sampled between April 2011 and April 2012. There were high levels of infection by S. musculosum metacercariae in the eyes of S. insculpta from all the sampled ecosystems, thus presenting broad geographical distribution. The histological analyses revealed that the metacercariae were apparently lodged behind the retina. The smaller fish from the Taquari River were less parasitized by metacercariae than the adults. This pattern can be explained by the cumulative effect of parasitism, as demonstrated by the positive correlation between the abundance of metacercariae and fish body size.

Novas ocorrências e efeitos do parasitismo por metacercárias em olhos de peixe têm sido recentemente discutidas em muitos estudos. O objetivo deste estudo foi avaliar os níveis de infecção dos vermes de olho Sphincterodiplostomum musculosum Dubois, 1936(metacercárias) em Steindachnerina insculpta(Fernádez-Yépez, 1948) de três ecossistemas influenciados pelo reservatório de Jurumirim (Rios Paranapanema, Taquari e Veados). Um total de 174 espécimes de peixes foi amostrado de Abril/2011 a Abril/2012. Metacercárias de S. musculosum mostraram altos níveis de infecção nos olhos de S. insculpta em todos os ecossistemas amostrados apresentando ampla distribuição geográfica. As análises histológicas revelaram que, aparentemente, estas metacercárias estavam alojadas por trás da retina. Os peixes menores do rio Taquari estavam menos parasitados por metacercárias do que os adultos. Esse padrão pode ser explicado pelo efeito cumulativo de parasitismo, evidenciado pela correlação positiva entre a abundância de metacercárias e tamanho do corpo dos peixes.
Keywords: Paranapanema River; Freshwater fish; Steindachnerina insculpta; Brazil; Rio Paranapanema; Peixe de água doce; Steindachnerina insculpta; Brasil